The significance of story telling in teaching listening - Azatova Nodira Anvarbek kizi (International Journal on Economics, Finance and Sustainable Development, 2021)
This article deals with firstly storytelling method of teaching and secondly provides some valuable recommendations and helpful suggestions. It also deals with the methodological and practical aspects of activities that are highly useful for listening skills and also motivational tools such as music, song, and video..